A MACH AIRSPEED WARNING SYSTEM A MACH AIRSPEED WARNING SYSTEM IN COCKPIT - Andre Wahyudi Sihombing; Muhammad Caesar Akbar (Jurnal Penelitian)
This research examines the Mach Airspeed Warning System on aircraft at PT. Batam Aero Technic as a hangar or aircraft maintenance service provider registered with the Ministry of Transportation. The Mach airspeed warning system supports an aural warning system to help turn on the aircraft when the aircraft is in a condition exceeding or approaching the airspeed limit which will later enter the Mach speed. The research method used is descriptive and qualitative. Beginning with the experience of any consequences related to the Mach Airspeed Warning System, then presenting solutions to the potential hazards carried out by the author so that these potential hazards can be reduced. The results of the study found 4 causes that made errors in Mach Airspeed.